Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.4081/hr.2009.e6
|View full text |Cite
|
Sign up to set email alerts
|

Human heart-type fatty acid-binding protein as an early diagnostic marker of doxorubicin cardiac toxicity

Abstract: Progressive cardiotoxicity following treatment with doxorubicin-based chemotherapy in patients with non-Hodgkin's lymphoma (NHL) may lead to late onset cardiomyopathy. So, early prediction of toxicity can lead to prevention of heart failure in these patients. The aim of this work was to investigate the role of H-FABP as an early diagnostic marker of anthracycline-induced cardiac toxicity together with brain natriuretic peptide (BNP) as an indication of ventricular dysfunction in such patients. Our study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…ElGhandour et al 72 studied H-FABP in 40 non-Hodgkin's lymphoma patients treated with 6 cycles of CT containing Doxorubicin (cumulative dose 300 mg/m 2 ). The authors concluded that H-FABP may serve as a reliable early marker for prediction of cardiomyopathy induced by Doxorubicin.…”
Section: Perspective Markers Of Ct-induced Cardiotoxicity (Under Study)mentioning
confidence: 99%
“…ElGhandour et al 72 studied H-FABP in 40 non-Hodgkin's lymphoma patients treated with 6 cycles of CT containing Doxorubicin (cumulative dose 300 mg/m 2 ). The authors concluded that H-FABP may serve as a reliable early marker for prediction of cardiomyopathy induced by Doxorubicin.…”
Section: Perspective Markers Of Ct-induced Cardiotoxicity (Under Study)mentioning
confidence: 99%
“…Heart-type fatty acid binding protein (H-FABP) is also a small cytosolic protein released in the circulation after cardiac damage. It has been studied in chronic heart failure as a marker of ongoing myocardial damage [15] but only evaluated in one small study in the setting of cardiotoxicity [16].…”
Section: Introductionmentioning
confidence: 99%
“…In 40 patients treated with AC-containing CT, FABP levels were measured within 24 h after CT; patients with significant (under the normal limit of 50%) LVEF reduction had higher FABP levels compared to those without evidence of cardiac dysfunction [59]. Elevation in GPBB, but not in FABP, was reported by…”
Section: Elevated Tni (N=36)mentioning
confidence: 94%